Everyday Ethnicity in Michigan’s Copper Country in the Early Twentieth Century - Huhta, Aleksi (fi=Turun yliopisto|en=University of Turku|, 2017)
Students of ethnicity have long grappled with the problem of essentialism. How to study ethnicity without reifying ethnic identities or reproducing the idea that ethnic groups are a natural feature of the social landscape? Recently, many scholars have argued for an increased focus on interactions rather than identities. This study takes up on this suggestion. It examines how ethnic boundaries are constructed, reproduced, and contested in everyday interactions. The empirical case at the center of this study concerns the early-twentieth-century Copper Country, a mining region in northwestern Michigan, United States. Copper Country was in the early 1900s home to a diverse population of immigrants from different parts of Europe. Rather than focus on the identity of a particular group, my study centers interactions between the different immigrants and the native-born population. It examines how people from different ethnic backgrounds understood their interactions with each other and how ethnic boundaries were constructed, and contested, in these interactions. My study indicates that ethnic boundaries were often less socially consequential than is sometimes maintained in the scholarship on immigrant identities in the U.S.: while a meaningful cognitive framework in certain situations, ethnic boundaries became next to insignificant in others. The material for my study consists of interviews, collected in the 1970s as part of an oral history project “Finnish Folklore and Social Change in the Great Lakes Region.”